Re-imagining the other : culture, media, and western-muslim intersections - Eid, Mahmoud; Karim, Karim H.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This volume addresses the conceptualizations of the Other carried out by Western and Muslim societies historically and in contemporary times through empirical case studies.
Keywords: Science; Science; Science, general